AN EXPLORATORY STUDY OF FACTORS INFLUENCING PAKISTANI PHYSICIANS' RETENTION AND RESETTLEMENT CAREER DECISIONS - Arif, Muhammad; Fraser, John; Cruickshank, Mary (Journal of Ayub Medical College Abbottabad, 2022)
Background: The recruitment, retention and migration of health workers is a global phenomenon. The literature shows push factors associated with leaving rural areas and developing countries in general are explored in depth. However importantly, some health workers behave differently and decide to stay in or return to a developing country. Less is known about the reasons/ pull factors of this groups' decision making. Methods: This paper aims to explore the perceptions of Pakistani physicians regarding their career decisions to remain in their country, or resettle back after working abroad for some time. Thirteen Pakistani physicians were interviewed via telephones who were working in Pakistan and Australia. Results: The motivation for Pakistani physicians to remain or resettle back into their country stems from the perceived better quality of life in Pakistan compared to the better standard of life overseas. Other reasons include a perceived differentiation between locals and non-locals abroad and the availability of a permanent job in Pakistan. Conclusion: The main factors that contributed to Pakistani physicians' retention and resettlement decisions were mostly personal and family or societal factors and there was a minimal role for professional or health system related factors in their career decisions, except for the availability of permanent jobs in Pakistan.